1982
DOI: 10.1159/000261666
|View full text |Cite
|
Sign up to set email alerts
|

Declination: Construct or Intrinsic Feature of Speech Pitch ?

Abstract: Declination is taken as the focus of studying pitch phenomena from an acoustic, physiological and perceptual point of view. It is shown that originally declination was no more than a theoretical construct to account for the interpretation of acoustic F₀ recordings. Recently, psycholinguistic considerations have enhanced the domain of application so as to account for this phenomenon. The literature is reviewed and the authors take issue over the various claims put forward by others, such as the dominance of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(40 citation statements)
references
References 6 publications
3
37
0
Order By: Relevance
“…A post hoc pairwise comparison (Table 3) confirms that a word has higher MaxF0 when its accent is further away from word end (p < 0.05), except that pitch accents that are 3 or 4 morae away do not have significantly different MaxF0. Note that this cannot, at least not solely, be attributed to the well-known phonetic phenomenon of declination (Cohen et al, 1982;Ladd, 1984), or else words of the same accent condition but different lengths would have the same peak height. In fact, Figures 3 and 5 show that Pre-Low Raising in Japanese Pitch Accent confirms that different peak-to-end distance conditions have significantly different MinF0A, except for those that are 3 morae and 4 morae away from the word end, in which case they are not significantly different, as is the case for MaxF0.…”
Section: Resultsmentioning
confidence: 99%
“…A post hoc pairwise comparison (Table 3) confirms that a word has higher MaxF0 when its accent is further away from word end (p < 0.05), except that pitch accents that are 3 or 4 morae away do not have significantly different MaxF0. Note that this cannot, at least not solely, be attributed to the well-known phonetic phenomenon of declination (Cohen et al, 1982;Ladd, 1984), or else words of the same accent condition but different lengths would have the same peak height. In fact, Figures 3 and 5 show that Pre-Low Raising in Japanese Pitch Accent confirms that different peak-to-end distance conditions have significantly different MinF0A, except for those that are 3 morae and 4 morae away from the word end, in which case they are not significantly different, as is the case for MaxF0.…”
Section: Resultsmentioning
confidence: 99%
“…In 1999, Ladd et al found weak evidence for a relationship between pitch excursions and speech rate. Another reported pitch range-timing relationship illustrates that the interval between onset and offset frequency in an utterance increases with duration (Cohen et al, 1982). The role of gender in either of these relationships was not examined.…”
Section: Pitch Range and Timementioning
confidence: 99%
“…Declination refers to the downward trend of F 0 over the course of an utterance [1,2]. It was found that declination was expected and used for normalization by listeners, i.e., when two stressed syllables sounded equal in pitch, the second was actually lower [3].…”
Section: Introductionmentioning
confidence: 99%